Gimnasia cerebral y el desarrollo psicomotor en los niños de 4 a 5 años de la Escuela de Educación Básica Filomena Rojas Ocampo de la ciudad de Loja, periodo académico 2021-2022. - Masa Ramón, Alexandra Elizabeth (2022)
Psychomotor development is the progressive acquisition of skills that go through a certain level of difficulty until they can be perfected and become the basis of basic skills, so it is essential to stimulate the nerve structures with techniques or methods that allow their evolution in a natural way, so that children acquire significant learning throughout their lives; For this reason, the research is aimed at determining the incidence of Brain Gymnastics in the Psychomotor Development of children aged 4 to 5 years of the Filomena Rojas Ocampo School of Basic Education, in the city of Loja, academic period 2021-2022. This research is quantitative with a type of descriptive scope and a quasi-experimental design; the methods used for its development were: inductive, deductive, analytical-synthetic. For the initial and final diagnosis of the psychomotor profile, the Victoria de la Cruz and Carmen Mazaira Preschool Psychomotricity Assessment Scale (EPP) instrument was applied to 16 children. The results of the same show that: 53% of children presented a low level and only 10% good, for which an activity guide entitled "Mind, body and movement" was developed; Once applied, a significant improvement is evident, since: 70% of children were in the good level, while 7% in low. Brain gymnastics contributes to the continuous acquisition of psychomotor skills of typical and atypical children, since it allows their knowledge to occur spontaneously through the exploration and recognition of their own body. Keywords: brain gymnastics, psychomotor development, psychomotor mastery, body movement, brain and learning.